Literacy dan Income Terhadap Pinjaman Online Pada Generasi Milenial - Dantowi Dantowi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of digital technology has changed many aspects of life, including in the financial sector, because now there has been a Lending Loan Platform or Financial Technology (Fintech) Lending. Online loans provide easy access and processes, so it becomes an interesting alternative, especially for the Millennial generation. That way the millennials must have the ability of individuals to understand and manage personal finance, which includes skills to identify risk, interest, and obligations in every financial transaction. Then the combination of good financial literacy and stable income is the key to the use of healthy and responsible online loans.